PERAN INTELLECTUAL CAPITAL DALAM PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP FINANCIAL PERFORMANCE - Nony Kezia Marchyta; Njo Anastasia (Politeknik Negeri Batam, 2021)
The objective of this research is to observe the direct impact of corporate social responsibility towards financial performance, and indirect impact of corporate social responsibility towards financial performance through intellectual capital and bankruption risk as mediating variables. Smart PLS software is used in this study. Data is obtained from annual report of banking companies listed in IDX from 2011 to 2018. This study is a quantitative form which is calculated using Corporate Social Disclosure Index formula as CSR indicator, Value Added Intellectual Coefficient (VAICTM) as indicator of intellectual capital, Tobin’s Q as financial performance indicator. The results show positive impact of corporate social responsibility towards financial performance, corporate social responsibility towards intellectual capital, and intellectual capital towards financial performance.